NILAI PENDIDIKAN KARAKTER DALAM NOVEL GURU AINI KARYA ANDREA HIRATA - Fernanda Venturini; Muhammad Saleh; Hajrah Hajrah (Universitas Negeri Makassar, 2022)
The Value of Character Education in the Novel Guru Aini by Andrea Hirata. This study aims to describe the value of character education. This type of research is a descriptive qualitative approach. The data source in this research is the novel Guru Aini by Andrea Hirata. Data collection is done by using documentation techniques. The data obtained were analyzed in three stages, namely: data reduction, data presentation, and drawing conclusions. The results showed that in this novel, there are five main character education values, namely religious, nationalist, independent, mutual cooperation, and integrity. when transformed into 18 values of character education, religious values are found, honesty, tolerance, discipline, hard work, creative, independent, democratic, curiosity, national spirit, love for the homeland, respect for achievement, friendly/communicative, peace-loving, fond of reading , care for the environment, care for social, and responsibility. Furthermore, there are five methods of character education, namely teaching, lots of example, lots of motivation, lots of habituation, and lots of rule approaches.